1999
DOI: 10.1097/00007890-199911270-00018
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Lung Transplants to Preformed Donor-Specific Hla Antibodies as Detected by Flow Cytometry

Abstract: Class II, and perhaps class I HLA antibodies at relatively low concentrations represent a risk factor for severe early pulmonary graft dysfunction, with the potential to progress to hyperacute rejection and death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 18 publications
2
42
0
Order By: Relevance
“…Development of Abs against the donor-mismatched HLA Ags has been shown to correlate with the development of chronic rejection in transplant recipients, and the development of Ab has been shown to precede clinical evidence of chronic rejection (12,21). Studies from our laboratory (11) and others (22)(23)(24) have demonstrated that posttransplant development of anti-HLA Abs correlate with development of BOS following human lung transplantation. However, a substantial proportion of the transplant recipients, despite the absence of development of any detectable Abs against donor-mismatched HLA Ags, undergo chronic rejection, and in many of these cases Ab as well as complement deposition have been observed in their grafts (25)(26)(27).…”
Section: Discussionmentioning
confidence: 95%
“…Development of Abs against the donor-mismatched HLA Ags has been shown to correlate with the development of chronic rejection in transplant recipients, and the development of Ab has been shown to precede clinical evidence of chronic rejection (12,21). Studies from our laboratory (11) and others (22)(23)(24) have demonstrated that posttransplant development of anti-HLA Abs correlate with development of BOS following human lung transplantation. However, a substantial proportion of the transplant recipients, despite the absence of development of any detectable Abs against donor-mismatched HLA Ags, undergo chronic rejection, and in many of these cases Ab as well as complement deposition have been observed in their grafts (25)(26)(27).…”
Section: Discussionmentioning
confidence: 95%
“…Preformed anti-donor class II antibodies increase the risk of transplant failure [1][2][3][4][5][6][7][8][9] and the post-transplant development of anti-class II antibodies is associated with a higher incidence of acute and chronic rejection [10][11][12][13][14][15][16][17][18][19] Current class II matching strategies for kidney transplantation consider only the HLA-DR antigens controlled by the DRB1 locus but mismatching for HLA-DQ and HLA-DP may also lead to lower graft survival rates [20][21][22][23][24][25]. Newer serum screening methods such as ELISA, Flow Cytometry and Luminex have greatly enhanced the detection of anti-HLA-DQ and HLA-DP antibodies and their association with transplant rejection [2,7,[26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies to the 60QF epitope have been described previously and were found in 32% of patients with a failing kidney allograft. 21 In cohort studies on lung transplantation, the effect of pre-existing donor-specific anti-HLA antibodies on rejection and (graft) survival is difficult to evaluate, because only 5% to 15% of patients have elevated PRA levels prior to transplantation, 5,14,15 in contrast to 25% to 50% of kidney transplant patients on the waiting list. 22 Nevertheless, in two large studies (656 and 10,000 patients, respectively), decreased survival was reported in lung transplant recipients with a pre-transplant PRA exceeding 25%.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies could not identify differences in graft failure between sensitized and unsensitized patients, 6,13 most have shown that antibodies against HLA are associated with early graft dysfunction and decreased survival in lung transplant recipients. 5,14,15 However, these studies did not discriminate between donor-specific and non-donor-directed HLA antibodies. The effect of PRA on the allograft might therefore be due to donor-specific anti-HLA antibodies, but the concordant existence of antibodies toward non-HLA antigens or a general increased immune responsiveness could also play a role.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation